Emotional eating experiences among first-year medical students: A qualitative study - Muhammad Zaidan Afkar; Sri Maria Puji Lestari; Nia Triswanti; Okta Reni Setiawati (Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Unit Penelitian dan Pengabdian Kep Akademi Keperawatan Baitul Hikmah, 2026)
Background: Emotional eating is an eating behaviour triggered by emotional states rather than physiological hunger. Academic stress experienced by first-year medical students may increase the tendency to engage in emotional eating, potentially affecting their physical and psychological well-being. Purpose: To explore emotional eating behaviour among first-year medical students. Method: An exploratory design. Data were collected through focus group discussions (FGDs) involving first-year medical students at the Faculty of Medicine, Universitas Malahayati. Data were analysed using descriptive thematic analysis supported by source triangulation and relevant literature. Results: Emotional eating was commonly reported as a response to academic stress and adaptation challenges during the first year of medical education. Participants described changes in eating behaviours, including overeating, increased consumption of sweet foods, eating in response to negative emotions, and impulsive eating. These behaviours were perceived to influence both physical health and emotional well-being. Conclusion: Emotional eating among first-year medical students functions as a coping strategy for academic stress and adaptation difficulties. Strengthening emotional regulation and providing psychological support may help reduce emotional eating behaviours and promote healthier coping mechanisms. Keywords: Academic Stress; Coping Behaviour; Emotional Eating; First-Year Medical Students; Qualitative Study.